DEVELOPING HIGH SCHOOL MATHEMATICS LEARNING MODELS BASED ON PEDAGOGICAL CONTENT KNOWLEDGE PROFESSIONAL MATHEMATICS TEACHERS - Purwoko, Riawan Yudi; Wibowo, Teguh; Astuti, Erni Puji; Purwaningsih, Wharyanti Ika (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Pedagogical content knowledge is teachers’ knowledge and experience in teaching specific content. However, professional mathematics teachers have not used it as a basis for information in developing mathematics learning models. This study aims to produce a mathematics learning model based on the knowledge and experience of professional teachers in teaching sequences and series. This study uses a development model with the Plomp scheme, which consists of 5 stages: initial investigation, design, realization/construction, testing, and implementation. The subjects in this study were eight high school teachers who have experience and excellent reputations. Data collection techniques are documentation, FGD, observation, questionnaires, and tests. The data analysis in this study was qualitative, using percentage-based techniques and vignette analysis of learning outcomes. The results showed that after the needs analysis, realization, and design stages, the product was tested through expert reviews and assessments. The assessment results showed that the product was valid and practical. The implementation stage was conducted in 3 schools, with 147 students as research participants. The results showed that the developed model had a positive, potential impact, as students were more constructive in their learning. Thus, the developed model can serve as a reference for mathematics learning, particularly for sequences and series. During the learning process, students are more creative and constructive, and follow the concept of in-depth learning in a pedagogical context.